2022
DOI: 10.3390/molecules27030702
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Cannabinoid CB2 Receptor Agonists from Botanical Compounds and Preliminary Evaluation of Their Anti-Osteoporotic Effects

Abstract: As cannabinoid CB2 receptors (CB2R) possess various pharmacological effects—including anti-epilepsy, analgesia, anti-inflammation, anti-fibrosis, and regulation of bone metabolism—without the psychoactive side effects induced by cannabinoid CB1R activation, they have become the focus of research and development of new target drugs in recent years. The present study was intended to (1) establish a double luciferase screening system for a CB2R modulator; (2) validate the agonistic activities of the screened comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“… 35 On the other hand, studies have shown that TPRV1 activation caused release of inflammatory cytokines, while CB2 receptor activation prevented local and systemic immune response. 36 , 37 These earlier studies prompted us to focus on the roles of CB2 receptor and TRPV1 in the anti-inflammatory action of CBD. In our study, the expression of CB2 receptor and TRPV1 in keratinocytes was confirmed and the effects of antagonists of the two receptors were studied.…”
Section: Discussionmentioning
confidence: 99%
“… 35 On the other hand, studies have shown that TPRV1 activation caused release of inflammatory cytokines, while CB2 receptor activation prevented local and systemic immune response. 36 , 37 These earlier studies prompted us to focus on the roles of CB2 receptor and TRPV1 in the anti-inflammatory action of CBD. In our study, the expression of CB2 receptor and TRPV1 in keratinocytes was confirmed and the effects of antagonists of the two receptors were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Targets were collected from DrugBank (n ¼ 235), Genecards (n ¼ 1,173), OMIM (n ¼ 11), PharmGKB (n ¼ 12), and TTD (n ¼ 30); the reference targets were investigated in Pubmed, including CNR2, EFNB2, EPHB4, ITGB1, NFE2L2, GSK3B, FOXF2, SIRT3, TSC1, BHLHE40, GSTM1, and TFRCU. [19][20][21][22][23][24][25][26][27][28][29] We identified 1,374 targets related to OP after deleting duplicates. We searched for the 85 DZ targets checked by UNIFI from ETCM, HERB, and SwissTargetPrediction.…”
Section: Gene Selection and Network Generationmentioning
confidence: 99%
“…Firstly, minimizing the target protein free energy with Chem3D, the target proteins were introduced into AutoDock-Tools (Version: 1.5.7), where water molecules and original ligands in the target proteins were removed, and hydrogen atoms were added, then docking box generation within 40 Å with the original ligand as the center. The active ingredients that can bind to these targets were used as ligands, and the 3D molecular conformations of the ingredients were then obtained from the PubChem Compound database [43]. Subsequently, the docking experiments were achieved with the help of AutoDock Vina in a semiflexible 2.2.6.…”
Section: Prediction Of Potentialmentioning
confidence: 99%